Kinetische Untersuchung zur Oxidation von Sulfhydrylverhindungen im heterogenen System durch Reaktionsspektren und Extinktionsdiagramme - Heinz Mauser; Jürgen Polster; Helmut Wenck (CHIMIA)
In the reaction of the aromatic mercaptan, 4-mercapto acetanilide in neutral and alkaline medium, it can be shown on the basis of the reaction spectrum and the spectrum of 4-hydroxy acetanilide that substitution reactions do not take place. From mass spectra it is evident that oxidation to disulfide occurs which is followed by the precipitation of the disulfide as fine needle-shaped crystals. The E- and EDQ-diagrams show that the reaction is not uniform, but consists of two reaction steps. The first step is the oxidation and the second the precipitation.